THE EFFECT OF ADDITION OF LIME (Citrus aurantifolia) ON THE QUALITY OF NILA FISH (Oreochromis niloticus) DURING STORAGE AT ROOM TEMPERATURE - Putri, Thesia Maharani; Leksono, Tjipto; Syahrul, Syahrul (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractThis research aims to determine the effect of adding lime (Citrus aurantifolia) juice on the quality of nila fish (Oreochromis niloticus) during storage at room temperature. The research method was used an experimental method, which is to lubricate fresh nila fish with various concentrations of lime juice and stored at room temperature. This research was carried out in stages by conducting preliminary research to determine the best lime concentration and continued to the main research. The research data were analyzed using a non factorial randomized block design (RBD). The parameters tested were organoleptic (appearance, texture, aroma, and taste), Total Plate Count (TPC), water activity (aw), and pH level. Research shows that the use of lime juice has a significant effect on the quality of nla fish stored at room temperature with a concentration of 50% lime juice as the best treatment with characteristics: elastic texture, slightly dense, compact, fresh sour, delicious, and specific fish taste that reshly added with lime acid, the TPC value was 38.10x102 colony / gram, the average pH value was 4.13, and the average aw value was 0.81 for storage for 0 hours to 12 hours.Keywords: lime, nila fish, quality, natural preservative.